Improving a patient's experience in a governmental hospital in Kazakhstan using modern it methods - Nurtazina, Dana (2014)
The health sector is one of the most intensive, where reliable and timely information is a critical resource for the monitoring of service provision at all levels. Being ‘indispensable’, modern IT is progressively providing us with the combination of tools and knowledge for improving health care, enabling the finding of correct solutions that benefit patients, healthcare institutions and professionals in many dimensions worldwide. This dissertation provides a thorough review of comprehensive health information systems, their importance in the health care sector and key findings from a patient-oriented survey. The findings of this dissertation offer a pilot project of health web portal implementation, considering national and economic realities, that is aimed to enhance patient experience of a real-world government hospital in Kazakhstan.